Diagnosis, assessment, and management of surgical complications following esophagectomy. Issue 1 (8th July 2018) - Grimminger, Peter P.; Goense, Lucas; Gockel, Ines; Bergeat, Damien; Bertheuil, Nicolas; Chandramohan, Servarayan M.; Chen, Ke‐neng; Chon, Seung‐hon; Denis, Collet; Goh, Khean‐lee; Gronnier, Caroline; Liu, Jun‐feng; et al.
Abstract: Despite improvements in operative strategies for esophageal resection, anastomotic leaks, fistula, postoperative pulmonary complications, and chylothorax can occur. Our review seeks to identify potential risk factors, modalities for early diagnosis, and novel interventions that may ameliorate the potential adverse effects of these surgical complications following esophagectomy. Abstract : Surgical complications, such as anastomotic leaks, fistulas, postoperative pulmonary complications, and chylothoraxes, can occur following esophagectomy. This review seeks to identify potential risk factors, modalities for early diagnosis, and novel interventions that may ameliorate the potential adverse effects of these complications.